Metallic Nanoparticles Applications in Neurological Disorders: A Review - Ernesto Ibarra-Ramírez; Melissa Montes; Roger Alexei Urrutia; Diego Reginensi; Edwin A. Segura González; Luis Estrada-Petrocelli; Alexandra Gutierrez-Vega; Abhishek Appaji; Jay Molino (International Journal of Biomaterials, 2025)
Metallic nanoparticles (NPs) possess unique physicochemical properties that have enabled their engineering for loading drugs, contrast agents, and targeting moieties for cellular and intracellular components, highlighting their emerging role as versatile tools in managing neurological disorders. In therapeutic applications, the surface plasmon resonance characteristics of gold and silver NPs and the responsiveness of magnetic nanoparticles (MNPs) to external magnetic fields facilitate the disruption of protein aggregates and the eradication of cancer cells. For diagnostic purposes, the inherent high electron density of metallic NPs makes them effective contrast agents in imaging technologies. Moreover, these NPs have proven their capability to traverse the blood–brain barrier (BBB) and interact with central nervous system (CNS) components. Despite their extensive scientific exploration and promising applications, metallic NPs have not yet achieved widespread clinical implementation, especially in comparison to polymer-based NPs. This article presents an in-depth examination of the physicochemical properties of metallic NPs relevant to neurological applications. It summarizes their roles in diagnosis and therapy, focusing on gold, magnetic, silver, titanium, and cerium NPs. Additionally, this document explains the incorporation of metal NPs in their application and their effect on the human body.